(untitled) (Journal of Nepal Geological Society, 2019)
Geomorphometric properties of watershed-scale are often calculated to characterize drainage basins morphology for evaluating their geomorphic status of basin development. More recently these properties have widely been applied in inferring the sediment delivery ratio and sediment yields of the basin to estimate and know sediment erosion status of drainage basin with the help of morph metric data. In fact, sediment delivery ratio (SDR) and specific sediment yield (SSY) of the basins depend not only on watershed properties but also indirectly on other factors such as climate, hydrology, land use and geology, which can be of low variation for a small watershed. The aims of the present study were to compute some of the geomorphometric parameters of the Karra River Basin (KRB), located in Hetauda, Makawanpur District, Central Nepal, to compare some of these among the sub-basins with varying geology, touse some of parameters in estimating sub-basin-wide SDR and SSY using empirical equations and to infer geomorphic development and erosion status of the basin. Based on hypsometric analysis, the southern sub-basins with mainly gravelly terrain are mostly of mature to unstable phase, whereas the northern sub-basins with bedrocks of the Lower and the Middle Siwalik Subgroups are of Monadnock phase to mature stage of basin development. Sediment delivery ratio (SDR) and specific sediment yield (SSY) estimated for the southern sub-basins of the KRB are relatively lower compared to those estimated for the northern sub-basins. Considering the geology of the KRB and hypsometric integral, although the SDR and SSY of the southern sub-basins are lower compared to the northern sub-basins, the southern sub-basins are vulnerable to erosion because of their unstable geomorphic development stage and pervasive distribution of unconsolidated weak sediments having high erodibility.